2011
DOI: 10.1016/j.juro.2011.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin for Men With Chronic Prostatitis/Chronic Pelvic Pain Syndrome: Results of a Phase II Multicenter, Double-Blind, Placebo Controlled Study

Abstract: Silodosin 4 mg relieved symptoms and improved quality of life in men with chronic prostatitis/chronic pelvic pain syndrome but its efficacy requires confirmation in additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
1
46
0
2
Order By: Relevance
“…In all, 10 placebo-controlled RCTs (n = 58-272) were identified that evaluated a-adrenergic antagonists (tamsulosin [53][54][55], alfuzosin [56,57], doxazosin [58,59], terazosin [60,61] and silodosin [62]) in CBP and CP/CPPS. Most (eight) showed positive results, with significant differences vs placebo in NIH-CPSI total, urinary symptom, pain, and/or QoL scores [54][55][56][57]59,60], or in scores using other validated symptom scoring tools [58,61].…”
Section: A-adrenergic Antagonistsmentioning
confidence: 99%
“…In all, 10 placebo-controlled RCTs (n = 58-272) were identified that evaluated a-adrenergic antagonists (tamsulosin [53][54][55], alfuzosin [56,57], doxazosin [58,59], terazosin [60,61] and silodosin [62]) in CBP and CP/CPPS. Most (eight) showed positive results, with significant differences vs placebo in NIH-CPSI total, urinary symptom, pain, and/or QoL scores [54][55][56][57]59,60], or in scores using other validated symptom scoring tools [58,61].…”
Section: A-adrenergic Antagonistsmentioning
confidence: 99%
“…Silodosin at 4 mg was shown to be more effective than placebo in improving CPSI (statistical significance achieved within the urinary symptom and quality-of-life impact domains). GRA was also significantly greater for the treatment group (56% for 4 mg of silodosin vs 34% for placebo) [30]. The differences in treatment effects observed in this and other α-blocker studies, as explained by the authors, may be due to differences in study design, α-blockers, and study population.…”
Section: Management Of Lower Urinary Tract Symptoms Associated With Umentioning
confidence: 41%
“…Nickel et al reported in their research that Silodosin was effective for improvement of symptom and quality of life of in patients with CP/CPPS [14]. And it was further reported that terazosin [15] and alfuzosin [16] that are alpha blockers are also effective.…”
Section: Monotherapymentioning
confidence: 96%
“…The CPSI score had shown dramatic change [36]. Other options such as tadalafil which is a PDE5 inhibitor, which can treat erectile dysfunction, lower urinary tract symptoms and possibly the symptoms of CP/CPPS as well [37].…”
Section: 3-1 U: Urinarymentioning
confidence: 99%